1999
DOI: 10.1096/fasebj.13.14.2061
|View full text |Cite
|
Sign up to set email alerts
|

HSP27 inhibits cytochrome c‐dependent activation of procaspase‐9

Abstract: We have previously shown that the small heat shock protein HSP27 inhibited apoptotic pathways triggered by a variety of stimuli in mammalian cells. The present study demonstrates that HSP27 overexpression decreases U937 human leukemic cell sensitivity to etoposide-induced cytotoxicity by preventing apoptosis. As observed for Bcl-2, HSP27 overexpression delays poly(ADP-ribose)polymerase cleavage and procaspase-3 activation. In contrast with Bcl-2, HSP27 overexpression does not prevent etoposide-induced cytochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
339
4
14

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 456 publications
(366 citation statements)
references
References 41 publications
9
339
4
14
Order By: Relevance
“…Interestingly, by overcoming phosphorylation-driven dissociation of larger oligomers, cell growth at con¯uence in vitro and in vivo restored the ability of HSP27 to inhibit cell death. We have recently shown that HSP27 could interfere with the ®nal pathway to apoptotic cell death by preventing procaspase-9 and procaspase-3 activation, downstream of cytochrome c release from the mitochondria (Garrido et al, 1999). Accordingly, the wild type HSP27 and the alanine mutant, that forms small and large oligomeric structures, but not the aspartate mutant that only forms small oligomers, prevented caspase-3 and -9 activation induced either by exposure of cultured cells to cisplatin or by treating cell-free extracts with cytochrome c and dATP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, by overcoming phosphorylation-driven dissociation of larger oligomers, cell growth at con¯uence in vitro and in vivo restored the ability of HSP27 to inhibit cell death. We have recently shown that HSP27 could interfere with the ®nal pathway to apoptotic cell death by preventing procaspase-9 and procaspase-3 activation, downstream of cytochrome c release from the mitochondria (Garrido et al, 1999). Accordingly, the wild type HSP27 and the alanine mutant, that forms small and large oligomeric structures, but not the aspartate mutant that only forms small oligomers, prevented caspase-3 and -9 activation induced either by exposure of cultured cells to cisplatin or by treating cell-free extracts with cytochrome c and dATP.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that overexpression of wild type HSP27 inhibited etoposide-induced apoptosis by preventing cytochrome-c mediated activation of caspase-9 and caspase-3 in the U937 human leukemic cell line (Garrido et al, 1999). To determine whether this inhibition could be con®rmed in REG cells, we used a cell-free system (Garrido et al, 1999).…”
Section: Hsp27 Mutants Differentially Prevent Reg Cell Apoptosis Indumentioning
confidence: 99%
See 3 more Smart Citations